The role of perceived risk as moderating the relationship between behavioural intentions to E-Money users in Padang city: adoption of the UTAUT model 1 - Anisya Tri Wahyuni; Perengki Susanto (Universitas Negeri Padang, 2022)
In recent years, today's technological developments are growing rapidly. Financial services have used technology as an intermediary for transactions, one of which is electronic money (E-money). This study examines the limits of user behavioral intentions and actual behavior of using e-money services in the city of Padang. In addition, since there is limited research on the effect of moderation, this study introduces risk perception as a moderator, supported by the acceptance of relevant technologies and behavioral theories. using quantitative methods with Smart-PLS. Approach to analysis technique of 230 respondents. Determination of the sample in this study using purposive sampling method with Hair Theory calculation technique. The findings of this study indicate (i) Performance expectancy has a positive and significant effect on behavioral intention (ii) Effort expectancy has a positive and significant effect on behavioral intention (iii) Social influence has a positive and significant effect on behavioral intention (iv) Facilitating condition has a positive and significant effect on behavioral intention (v) Perceived risk is not proven as a moderator variable in the influence of behavior intention on use behavior.